Zeus and the Giant Iced Tea - Leopold McGinnis (Mingling Voices, 2011)
Crafting wings out of wax and poems from the underground, Zeus and the Giant Iced Tea is a dreamlike voyage through poetic narrative format, blurring the line between poetry and fiction. Exploring the frenetic lives of Mexican cowboys, robots, sultans, Greek gods, and convenience store clerks, Zeus and the Giant Iced Tea shatters preconceived notions of poetry and instead offers a more accessible strain of literary free flow.